2009
DOI: 10.1111/j.1464-410x.2009.08356.x
|View full text |Cite
|
Sign up to set email alerts
|

Have phosphodiesterase‐5 inhibitors changed the indications for penile implants?

Abstract: OBJECTIVE To evaluate the indications for penile prosthesis implantation in the treatment of erectile dysfunction (ED) before and after the introduction of sildenafil. PATIENTS AND METHODS Penile prosthesis implantation was indicated in 144 men with ED at our institution between 1992 and 2007; 83 (55.6%) accepted the procedure, 55 (38.2%) refused it and six (4.2%) accepted but eventually had no surgery. Sixty‐seven patients were operated primarily, and the remainder were referred cases with complications after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Improvement in erectile function was achieved in 45–67%, and successful intercourse was feasible in only 40–55% [5]. Interestingly, Cortes‐Gonzalez and Glina found that the proportion of men who underwent radical pelvic surgery that went on to penile implant surgery actually increased after the introduction of PDE5i, and the proportion of men who had ED caused by vascular diseases decreased [33]. Stanley et al.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in erectile function was achieved in 45–67%, and successful intercourse was feasible in only 40–55% [5]. Interestingly, Cortes‐Gonzalez and Glina found that the proportion of men who underwent radical pelvic surgery that went on to penile implant surgery actually increased after the introduction of PDE5i, and the proportion of men who had ED caused by vascular diseases decreased [33]. Stanley et al.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6] The introduction of PDE-5i revolutionised the management of ED. [7][8][9] Initially, PDE-5i reduced the number of men requiring penile prosthesis implantation. However, this trend has reversed recently, probably as a result of ED being marketed as a curable condition and more men seeking medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, this trend has reversed recently, probably as a result of ED being marketed as a curable condition and more men seeking medical treatment. [7][8][9] PDE-5i have also changed the indications for penile prosthesis as successful medical management of vascular ED, resulting in more prostheses being implanted following pelvic surgery. 8 Nevertheless, a small group of men will still require a prosthesis after failure of all other options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erectile function can be preserved after radical prostatectomy, depending upon previous potency status, the patient's age, tumor stage, and preservation of the neurovascular bundles (NVB) [2]. At best, the probability for potency recovery after bilateral NS-RRP in a referral center, in a patient younger than 60 years, having adequate erections preoperatively is 76%, while other studies, however, have reported much lower probabilities [3][4][5][6]. In accordance, despite the operative effort for bilateral anatomic preservation of the NVB, postoperative adequate erectile function cannot be guaranteed [2].…”
Section: Introductionmentioning
confidence: 99%